Prognostic value of the systemic immune-inflammation index in non-small cell lung cancer patients treated with immune checkpoint inhibitors: a systematic review and meta-analysis - Chen, Guorong; Bao, Bahu; Ye, Yucai; Hu, Aoyan; Sun, Jingzi; Liu, Weiying (Frontiers in Oncology, 2025)
BackgroundAlthough the systemic immune-inflammation index (SII) has emerged as a potential prognostic marker in various cancers, its specific role in non-small cell lung cancer (NSCLC) patients undergoing immunotherapy remains insufficiently explored. To address this critical gap, we conducted a comprehensive meta-analysis to assess the prognostic value of SII in NSCLC patients treated with immune checkpoint inhibitors (ICIs).MethodA comprehensive search was conducted across multiple databases—including PubMed, EMBASE, Cochrane and Web of Science—to identify relevant studies. Hazard ratios (HRs) and 95% confidence intervals (CIs) were pooled to evaluate the prognostic significance of SII for survival outcomes.ResultTen studies involving a total of 1,547 patients were included. High systemic immune-inflammation index (SII) was significantly associated with worse overall survival (OS) (HR=1.44, 95% CI=1.21–1.70, p < 0.001; I²=3.8%) and progression-free survival (PFS) (HR=1.44, 95% CI=1.21–1.71, p < 0.001; I²=37.2%). Subgroup analysis indicated that an SII >792 was significantly associated with poorer OS and PFS.ConclusionHigh SII is significantly associated with poorer OS and PFS, particularly when SII >792.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024586791, identifier RD42024586791.